A marketing plan for Companhia das Quintas to strengthen its position in the Chinese wine market - Cruz, Gonçalo Nogueira de Sousa Madeira (2014)
Companhia das Quintas, Limited Company wishes to conquer the Chinese market with its wines. For that, it decided to enter in a partnership with a local importer and distributor. This project analyses the macroeconomic factors of the country, the local market and the consumer behavior, using on-site research that included interviews with professionals of the industry, unstructured observation of the consumer and existing statistical data analysis. Finally, the project presents a marketing plan to make this partnership a success.